Expansive growth of two glioblastoma stem-like cell lines is mediated by bFGF and not by EGF - Podergajs, Neža; Brekka, Narve; Radlwimmer, Bernhard; Herold-Mende, Christel; Talasila, Krishna M.; Tiemann, Katja; Rajcevic, Uros; Lah, Tamara T.; Bjerkvig, Rolf; Miletic, Hrvoje (Radiology and oncology, 2013)
Background. Patient-derived glioblastoma (GBM) stem-like cells (GSCs) represent a valuable model for basic and therapeutic research. GSCs are usually propagated in serum-free Neural Basal medium supplemented with bFGF and EGF. Yet, the exact influence of these growth factors on GSCs is still unclear. Recently it was suggested that GBM stemlike cells with amplified EGFR should be cultured in stem cell medium without EGF, as the presence of EGF induced rapid loss of EGFR amplification. However, patient biopsies are usually taken into culture before their genomic profiles are defined. Thus, an important question remains whether GBM cells without EGFR amplification also can be cultured in stem cell medium without EGF.
Gesehen am 03.12.2021